(untitled) - Food and Agriculture Organization of the United Nations (Rome, 2007)
It comprise s of six selected country case study reports from Asia (Bangladesh, China, India, the Philippines, Thailand and Viet Nam) and an overall synthesis ending with conclusions and recommendations.
Keywords: Aquaculture industry,Aquaculture,Công nghiệp nuôi trồng thuỷ sản,Nuôi trồng thuỷ sản; Economic aspects,Lĩnh vực kinh tế; Asia,Asia,Châu Á,Châu Á